Ambient fine particulate matter exposure induces cardiac functional injury and metabolite alterations in middle-aged female mice. (May 2019) - Zhang, Yingying; Ji, Xiaotong; Ku, Tingting; Li, Ben; Li, Guangke; Sang, Nan
Abstracts: Plenty of epidemiological studies have shown that exposure to ambient particulate matter (PM2.5 ) is linked to cardiovascular diseases (CVDs) in older even in middle-aged populations; however, experimental evidence through intuitive metabolic analysis to confirm the age susceptibility and explain the related molecular mechanism of PM2.5 -induced cardiotoxicity is relatively rare. In the present study, C57BL/6 mice (adult (4-month) and middle-aged (10-month)) were given 3 mg/kg PM2.5 every other day by oropharyngeal aspiration for 4 weeks, and then, body and cardiac parameter, containing weight data, cardiac function, ultrastructure, metabolic analysis, and molecular detection were conducted to investigate the PM2.5 -induced cardiotoxicity. The results indicated that middle-aged mice were more susceptible to PM2.5, displaying slow cardiac growth, cardiac dysfunction, abnormal mitochondrial structure and function, and cardiac metabolic disorders. The altered metabolites were enriched in carbohydrate metabolism, fatty acid metabolism, amino acid metabolism, nucleotide metabolism and nicotinate and nicotinamide metabolism. In conclusion, we speculated that the cardiac metabolic disorders may be important factors in PM2.5 -induced cardiac dysfunction and mitochondrial structure destruction in middle-aged mice, providing a new direction for the study of the association between PM2.5 and CVDs. Graphical abstract: Image 1 Highlights: PM2.5 exposure changed the cardiac function and mitochondrial ultrastructure in middle-aged mice. PM2.5 exposure caused significant metabolic changes in the heart. Abnormal metabolites referred to carbohydrate, fatty acid, amino acid and nucleotide metabolism.